2018
DOI: 10.3390/f9060307
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Leaf Temperature between Lianas and Trees in the Neotropical Canopy

Abstract: Leaf temperature (T leaf ) influences photosynthesis and respiration. Currently, there is a growing interest in including lianas in productivity models due to their increasing abundance and their detrimental effects in the carbon stock of tropical ecosystems. Therefore, understanding the differences of T leaf between lianas and trees is important for future predictions of productivity. Here, we determined the displayed leaf temperature (T d = T leaf − air temperature) of several species of lianas and their hos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 47 publications
2
7
1
Order By: Relevance
“…Our study has documented that in general, liana-infested areas have a higher mean temperature than non-liana infested areas in the Santa Rosa National Park Environmental Monitoring Super Site. This temperature difference corroborates field-based observations by Sanchez-Azofeifa et al [24] and Guzmán et al [25], who also observed that, on average, liana leaves have a higher temperature than tree leaves in a Panamanian tropical dry forest.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our study has documented that in general, liana-infested areas have a higher mean temperature than non-liana infested areas in the Santa Rosa National Park Environmental Monitoring Super Site. This temperature difference corroborates field-based observations by Sanchez-Azofeifa et al [24] and Guzmán et al [25], who also observed that, on average, liana leaves have a higher temperature than tree leaves in a Panamanian tropical dry forest.…”
Section: Discussionsupporting
confidence: 90%
“…The mean temperature difference between the liana-infested and the non-liana infested areas in our study is smaller than what was observed in previous studies by Sanchez-Azofeifa et al [24] and Guzmán et al [25]. Despite the observed small temperature differences, such differences can be important to enhance the current ability to detect the presence of lianas by remote sensing.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…This would allow microclimate ecology to be integrated into classical landscape ecology and metacommunity dynamics (Hesselbarth et al, 2019;Senior et al, 2019), and also guide efforts to restore and increase connectivity in fragmented landscapes (e.g., through the rehabilitation of riparian buffer zones; Luke et al, 2019). It also provides an opportunity to assess the effectiveness of different forest and plantation management practices that aim to restore microclimate regimes by altering canopy structure and ecophysiology, such as natural regeneration, enrichment planting, and climber cutting (Rodríguez-Ronderos et al, 2016;Ichihashi et al, 2017;Guzmán et al, 2018). Moreover, this would also provide an opportunity to understand how different management interventions alter specific facets of microclimate (e.g., impact of liana cutting on transpiration) and whether these can be tailored to restore specific microclimatic conditions.…”
Section: Guiding Conservation and Restoration Efforts In Human-modifimentioning
confidence: 99%